If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -2 = 10x + -14 Reorder the terms: -2 + 12x = 10x + -14 Reorder the terms: -2 + 12x = -14 + 10x Solving -2 + 12x = -14 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -2 + 12x + -10x = -14 + 10x + -10x Combine like terms: 12x + -10x = 2x -2 + 2x = -14 + 10x + -10x Combine like terms: 10x + -10x = 0 -2 + 2x = -14 + 0 -2 + 2x = -14 Add '2' to each side of the equation. -2 + 2 + 2x = -14 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = -14 + 2 2x = -14 + 2 Combine like terms: -14 + 2 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| 300-6x=20+8x | | 30-42=55-d | | 3x+(34)x-(40)x=0 | | -x+10=-x+12 | | 5k^2+35k-40=0 | | 4(2z+1)=6z+15 | | f(30)=1.8c+32 | | X-8Y=-14 | | 35x-321=-789 | | 2.5x-18=x+12 | | -4(3(y)-1)=0 | | sqrt(4x^2+16y^2)=0 | | -11=5+3 | | 2w-2=-38 | | 10b-45=36-45 | | -4(3(5x)-1)=0 | | 3m-4=m+8 | | 7=2z+4 | | 1+x=24 | | -2=9-5n | | 8(3X-9)=2(12X+2) | | -13+3n=8n-8 | | 0=x^2+kx+2k-3 | | 3(x-4)+2a=5x+4 | | x+7.6=11.7 | | -3x+1=5x+17 | | 15+[-3]+(15)= | | -8+b=2 | | 15+(-3)+(15)= | | 96b=6 | | 2x-4(3x+5)=20 | | 11x^2=7-2 |